Система распознавания эмоций по голосу на основе сверточной нейронной сети - Марчуков, В. Ю. (Марчуков В. Ю. Система распознавания эмоций по голосу на основе сверточной нейронной сети / В. Ю. Марчуков // Радіоелектроніка та молодь у ХХI столітті : матеріали 25-го Міжнар. молодіжн. форуму, 20–21 квітня 2021 р. – Харків : ХНУРЕ, 2021. – Т. 3. – С. 65–66., 2021)
Emotion recognition by voice finds application in many areas: the development of social assistance robots, autonomous vehicles, equipment for neuro-feedback, etc. However, at the moment there is no sufficiently effective solution to this problem. According to recent studies, high efficiency in various tasks of recognition are convolutional neural networks.
Keywords: распознавание эмоций; эмоции